The Design of Permit Schemes and Environmental Innovation - Grischa Perino (University of Heidelberg, Department of Economics, 2008)
Most real world emission permit schemes are in effect hybrid instruments that feature both quantity and price controls. While the effects of price bounds are well understood for issues such as uncertain abatement costs it has not been investigated how such bounds affect time-consistency of environmental regulation and research incentives. The present paper analyzes these issues for two types of innovation. While price bounds increase static efficiency they reduce incentives to innovate. Commitment on details of a scheme's design might be necessary to avoid the latter.
Keywords: Q55; H23; O33; L51; 330; Environmental Regulation; Hybrid Instruments; Innovation; Time-inconsistency; Emissionshandel; Preis; Umweltstandard; Zeitkonsistenz; Umwelttechnik; Forschung; Anreiz; Theorie